The 2016 Mass Protests and the Responses of Security Forces in ANRS, Ethiopia: Awi and West Gojjam Zones in Focus - Atinafu, Kidanu (Ethiopian Journal of Social Sciences, 2021)
This study examined security forces’ abuse of power and their accountability in connection with the 2016 mass protests that unfolded in the Amhara National Regional State (ANRS) in general and Awi and West Gojjam Zones in particular. Specifically, the study assessed the nature of the use of force and the consequent investigations to punish security forces who abused their power. To address these objectives, the study employed a mixed methods research approach with a concurrent parallel design. Data for this research was obtained both from primary and secondary data sources. Interview, questionnaire and document analysis were used to collect data. A sample of 384 respondents was selected randomly to complete the questionnaire, whereas key informants were selected for the interview through snowball sampling technique. Based on the data gathered from all these sources, the study revealed that security forces committed arbitrary and extrajudicial killings and inflicted injuries against protesters who were chiefly unarmed and non-violent. The measures taken were found excessive and arbitrary with several civilians risking their lives and physical wellbeing. With few exceptions, the administrations at different levels of the government failed to investigate these extrajudicial and arbitrary killings and injuries inflicted in the process of punishing alleged perpetrators of the protest using civil and criminal laws. It is finally recommended to undertake independent investigations into the legitimacy of the murders, injuries, beatings and other forms of violence committed by the security forces.